La police du XVIIIᵉ siècle au miroir du Dictionnaire (1786-1789) de Des Essarts - Julien Broch (Journal of Interdisciplinary History of Ideas, 2023)
Between 1786 and 1789 Nicolas-Toussaint Lemoyne des Essarts published the seven volumes of his Police Dictionary. He was an employee of former chief of police Lenoir’s. The origin of the ‘police’ is the polis of the Ancient Greeks. It had reappared in French ordinances since the 15th century. It was maintained that a good police is based on the utility or the necessity of the commonweal. Police also meant regulatory power as well as administrative regulation. The cameral sciences influenced it. The police is a "science of detail" because each area of intervention is very specific. Each of them has a corresponding entry. Another objective of the work was to provide publicity for the Paris Metropolitan Police—by protecting the public order it would bring happiness to the inhabitants. This required territorialized action in every domain. Moreover, in order to standardize police practices, Essarts wanted to put in writing knowledge that had long been empirical.